Method for preparing porous copper foil based on sodium caseinate enhanced electrodeposition

By adding sodium caseinate and glycerin to the xanthan gum aqueous solution system, the stability and solubility of the aqueous solution are enhanced, and the problems of water sol dissolution difficulties and unstable configuration in the preparation of existing porous copper foils are solved, and the stable preparation of porous copper foil and the formation of multi-stage porous structures are achieved.

CN115261934BActive Publication Date: 2025-03-18QINGHAI INST OF SALT LAKES OF CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210838461.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-14
Publication Date
2025-03-18
Estimated Expiration
2042-07-14

AI Technical Summary

Technical Problem

In the existing porous copper foil preparation methods, the hydrosol has problems of dissolution difficulties and easy configuration changes during use, resulting in unstable preparation process.

Method used

Porous copper foil was prepared by electrodeposition in xanthan gum mesh long chain structure aqueous solution system enhanced by sodium caseinate. The stability of the aqueous solution system is enhanced by sodium caseinate bridging, and the dissolution process is accelerated under the action of glycerin additives.

Benefits of technology

The stable preparation of porous copper foil is achieved, and a multi-stage pore structure is formed on the surface, which has both micro-scale large pores and nano-size pores. The material exhibits a porous structure on both micro-nano scales.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115261934B_ABST
    Figure CN115261934B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing porous copper foil based on sodium caseinate-enhanced electrodeposition. The method comprises: providing an aqueous solution system containing xanthan gum, glycerol, sodium caseinate, sulfuric acid, and copper sulfate as an electrolyte, wherein the xanthan gum is in a long-chain network structure in the aqueous solution system and sodium caseinate is used as a bridge; the electrolyte, cathode, and anode are used to construct an electrochemical reaction system; and metal copper is deposited on the cathode surface by an electrodeposition method to prepare a porous copper foil. The method for preparing porous copper foil based on sodium caseinate-enhanced electrodeposition provided by the invention adds sodium caseinate to the xanthan gum long-chain network structure aqueous solution system, which can play a bridging role between xanthan gum molecular chains and significantly enhance the long-chain network structure of xanthan gum in the aqueous solution system; and a copper foil product with a porous surface can be prepared under the synergistic effect of the long-chain network molecule steric effect and the hydrogen bubble soft film board in the high-viscosity solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a porous copper foil, in particular to a method for preparing the porous copper foil by electrodeposition in a xanthan gum network long-chain structure aqueous solution system enhanced by sodium caseinate, belonging to the technical field of copper foil preparation. Background Art

[0002] Porous copper foil has a wide range of potential applications in electrocatalysis, sensors, negative current collectors for lithium-ion batteries, etc. Through the research of this team, among the current methods for preparing porous copper foil, the hydrosol template electrodeposition method has a good application effect. The hydrosol can form a mesh structure in the electrolyte and act as a template in the process of copper electrodeposition. The resulting porous copper foil has a complex structure in multiple dimensions.

[0003] The only drawback is that hydrosols are difficult to dissolve and their configuration is easily changed during use. Hydrosols are difficult to dissolve because they easily form a fish-eye structure during the dissolution process. The gel layer formed on the outer shell of the powder prevents water from entering its interior and causing dissolution. Summary of the invention

[0004] The main purpose of the present invention is to provide a method for preparing a porous copper foil by electrodeposition in a xanthan gum network long-chain structure aqueous solution system enhanced by sodium caseinate, thereby overcoming the shortcomings of the prior art.

[0005] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0006] The embodiment of the present invention provides a method for preparing a porous copper foil based on sodium caseinate-enhanced electrodeposition, which comprises:

[0007] Providing an aqueous solution system comprising xanthan gum, glycerol, sodium caseinate, sulfuric acid, and copper sulfate as an electrolyte, wherein the xanthan gum in the aqueous solution system is in a network-like long-chain structure with sodium caseinate as a bridge;

[0008] The electrolyte, cathode and anode jointly construct an electrochemical reaction system;

[0009] The porous copper foil is prepared by depositing metallic copper on the cathode surface by electrodeposition.

[0010] In some embodiments, the concentration of xanthan gum in the aqueous solution system is 0.5 mg / L to 200 mg / L, and the concentration of sodium caseinate is 0.1 mg / L to 200 mg / L.

[0011] The embodiment of the present invention also provides a porous copper foil having a porous surface which is prepared by the above-mentioned preparation method.

[0012] Compared with the prior art, the beneficial effects of the present invention are at least:

[0013] 1) The method for preparing porous copper foil based on sodium caseinate-enhanced electrodeposition provided by the present invention adds sodium caseinate to a xanthan gum network long-chain structure aqueous solution system, which can play a bridging role between xanthan gum molecular chains and significantly enhance the network long-chain structure of xanthan gum in the aqueous solution system; and a copper foil product with a porous surface can be prepared under the synergistic effect of the network long-chain molecule steric effect and the hydrogen bubble soft film board in the high-viscosity solution;

[0014] 2) Unlike conventional porous copper foils which have only a single porous structure, the copper foil prepared in the present invention has, in addition to the micron-sized macropores, a porous structure whose ligament portion is also composed of countless loose leaf-like structures, forming a nano-sized pore. The material exhibits a porous structure at both the micro- and nano-scales. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 It is a schematic diagram of the bridging effect of sodium caseinate in the xanthan gum network structure in a typical embodiment of the present invention;

[0017] Figure 2a-2c This is a SEM microstructure image of the porous copper foil prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0018] In view of the deficiencies in the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution mainly involves adding sodium caseinate to the xanthan gum hydrosol system, providing a method for preparing porous copper foil by electrodeposition in a xanthan gum network long-chain structure aqueous solution system enhanced by sodium caseinate.

[0019] The inventors of this case unexpectedly discovered that adding glycerol can effectively divide the hydrosol into countless interfaces at the microscopic level, avoiding the formation of fish-eye structures and accelerating its dissolution process. At the same time, the functional groups in glycerol can effectively bond with the hydrosol molecules to enhance the structure of the hydrosol. Experiments have found that it is difficult to form a stable hydrosol network structure under the action of glycerol alone, so sodium caseinate is added to the electrolyte. Sodium caseinate acts as a bridging agent between hydrosol molecules, further enhancing the stability of the hydrosol network structure and making the preparation conditions of the porous copper foil more stable.

[0020] The technical solution, its implementation process and principle will be further explained as follows.

[0021] One aspect of an embodiment of the present invention provides a method for preparing a porous copper foil based on sodium caseinate enhanced electrodeposition, comprising:

[0022] Providing an aqueous solution system comprising xanthan gum, glycerol, sodium caseinate, sulfuric acid, and copper sulfate as an electrolyte, wherein the xanthan gum in the aqueous solution system is in a network-like long-chain structure with sodium caseinate as a bridge;

[0023] The electrolyte, cathode and anode jointly construct an electrochemical reaction system;

[0024] The porous copper foil is prepared by depositing metallic copper on the cathode surface by electrodeposition.

[0025] In the method for preparing porous copper foil based on sodium caseinate-enhanced electrodeposition of the present invention, sodium caseinate is added to a xanthan gum and glycerol aqueous solution system. The bridging effect of sodium caseinate in the xanthan gum network structure is as follows: Figure 1 As shown. Sodium caseinate itself is a high molecular weight protein that can increase the viscosity of aqueous solutions. When used in combination with xanthan gum, due to the carboxyl groups in its structure, it can play a bridging role between xanthan gum molecular chains, significantly enhancing the network long chain structure of xanthan gum in the aqueous solution system. Under the synergistic effect of the network long chain molecule steric effect and the hydrogen bubble soft film board in the high viscosity solution, a copper foil product with a porous surface can be prepared.

[0026] In some preferred embodiments, the method comprises:

[0027] Mixing sulfuric acid and copper sulfate to form a mixed aqueous solution;

[0028] Mix xanthan gum, sodium caseinate and glycerin, add water, and stir thoroughly to dissolve to form an aqueous solution containing xanthan gum, sodium caseinate and glycerin;

[0029] The aqueous solution containing xanthan gum, sodium caseinate and glycerol is added to the mixed aqueous solution, and stirred for dissolution for 2 to 30 minutes to obtain an aqueous solution system containing xanthan gum, glycerol, sodium caseinate, sulfuric acid and copper sulfate.

[0030] In some preferred embodiments, the concentration of sulfuric acid in the mixed aqueous solution is 20 g / L to 150 g / L, and the concentration of copper sulfate is 10 g / L to 120 g / L in terms of copper ions.

[0031] In some preferred embodiments, the mass ratio of the glycerol in the total mass of xanthan gum, sodium caseinate and glycerol is 30% to 90%.

[0032] In some preferred embodiments, the volume ratio of water in the aqueous solution containing xanthan gum, sodium caseinate and glycerol is 40% to 95%.

[0033] In some preferred embodiments, the concentration of xanthan gum in the aqueous solution system is 0.5 mg / L to 200 mg / L, and the concentration of sodium caseinate is 0.1 mg / L to 200 mg / L.

[0034] In some preferred embodiments, the process conditions adopted by the electrodeposition method include: voltage of 1.0V to 3.8V, electrolysis temperature of 10°C to 60°C, and time of 10s to 5min.

[0035] In some preferred embodiments, the material of the cathode includes any one of copper, titanium, stainless steel, etc., but is not limited thereto.

[0036] Furthermore, the shape of the cathode includes a sheet shape or a cylindrical shape, but is not limited thereto.

[0037] In some preferred embodiments, the material of the anode includes an inert metal with an anti-corrosion coating on the surface. The inert metal may include any one of titanium, gold, platinum and the like, but is not limited thereto.

[0038] Furthermore, the shape of the anode includes a sheet shape or an arc shape, but is not limited thereto.

[0039] Among them, in some more specific implementation cases, the method for preparing porous copper foil based on sodium caseinate enhanced electrodeposition specifically includes the following steps:

[0040] Step 1: Use metal copper, titanium, stainless steel, etc. as the cathode, which can be in the shape of a sheet or a cylinder; use titanium or inert metals such as gold, platinum, etc. covered with an anti-corrosion coating as the anode, which can be in the shape of a sheet or an arc;

[0041] Step 2, using a mixed aqueous solution of sulfuric acid and copper sulfate as an electrolyte, wherein the concentration of sulfuric acid is between 20 and 150 g / L, and the concentration of copper sulfate is between 10 and 120 g / L (in terms of copper ions);

[0042] Step 3, xanthan gum, sodium caseinate and glycerol are mixed according to a proportion, wherein the total mass ratio of glycerol is usually between 30% and 90%;

[0043] Step 4, diluting the fully mixed xanthan gum and glycerin viscous material with water, wherein the amount of water added accounts for 40% to 95% of the volume of the entire system, and after fully stirring and dissolving, forming an aqueous solution of xanthan gum, sodium caseinate and glycerin;

[0044] Step 5, adding the aqueous solution of xanthan gum, sodium caseinate and glycerol to the mixed aqueous solution of sulfuric acid and copper sulfate, stirring and dissolving for 2 minutes to 30 minutes; the concentration of xanthan gum is between 0.5 mg / L and 200 mg / L; the concentration of sodium caseinate is between 0.1 mg / L and 200 mg / L;

[0045] Step 6: After the xanthan gum is fully dissolved in the sulfuric acid and copper sulfate solution, metallic copper is deposited on the cathode surface by electrodeposition, the cell voltage is between 1.0 and 3.8 V, the electrolysis temperature is between 10 and 60° C., and the time is between 10 s and 5 min. The obtained product is a porous copper foil.

[0046] Furthermore, another aspect of the embodiment of the present invention provides a porous copper foil with a porous surface prepared by the above-mentioned preparation method. In addition to the micron-sized macropores, the ligament part of the porous structure of the copper foil prepared by the present invention is also composed of countless loose leaf-like structures, forming a nano-sized pore, and the material presents a porous structure at both micro and nano scales.

[0047] In summary, through the above technical scheme, the method for preparing porous copper foil based on sodium caseinate-enhanced electrodeposition provided by the present invention adds sodium caseinate to the xanthan gum hydrosol system and applies it to the process of preparing porous copper foil by electrodeposition. Sodium caseinate can play a bridging role between xanthan gum molecular chains, significantly enhancing the network long chain structure of xanthan gum in the aqueous solution system; and copper foil with multi-level pores on the surface can be prepared under the synergistic effect of the network long chain molecule steric effect and the hydrogen bubble soft film board in the high viscosity solution.

[0048] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention is further described in detail below in conjunction with the accompanying drawings and several preferred embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. For the test methods in the following embodiments that do not specify specific conditions, the test methods in the embodiments are all carried out under normal conditions. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0049] All reagents used in the following examples were of analytical grade.

[0050] Example 1

[0051] Use metallic copper as the cathode, which is in the shape of a sheet; use platinum as the anode, which is in the shape of a sheet; use a mixed aqueous solution of sulfuric acid and copper sulfate as the electrolyte, wherein the concentration of sulfuric acid is 20g / L, and the concentration of copper sulfate is 120g / L (in terms of copper ions); mix xanthan gum, sodium caseinate and glycerol in proportion, with glycerol accounting for 30% of the total volume; add water accounting for 40% of the total volume, and stir to form a mixed aqueous solution of xanthan gum, sodium caseinate and glycerol. Add the solution to the mixed aqueous solution of sulfuric acid and copper sulfate, and stir to dissolve for 30 minutes; the concentration of xanthan gum is 200mg / L, and the concentration of sodium caseinate is 0.1mg / L; after the system is fully mixed, use electrodeposition to deposit metallic copper on the cathode surface, the cell voltage is 1.0V, the electrolysis temperature is 60°C, and the time is 5 minutes. The resulting product is a porous copper foil with good morphology. Figure 2a , Figure 2b and Figure 2c , which is a SEM microscopic morphology image of the porous copper foil in this embodiment.

[0052] Example 2

[0053] The cathode is a cylindrical one; the anode is an arc-shaped one with a metal titanium covered with an anti-corrosion coating; the electrolyte is a mixed aqueous solution of sulfuric acid and copper sulfate, wherein the concentration of sulfuric acid is 150 g / L and the concentration of copper sulfate is 10 g / L (in terms of copper ions); xanthan gum, sodium caseinate and glycerol are mixed in proportion, and the total volume ratio of glycerol is 90%; water accounting for 95% of the total volume is added, and a mixed aqueous solution of xanthan gum, sodium caseinate and glycerol is formed after stirring. The solution is added to the mixed aqueous solution of sulfuric acid and copper sulfate, and stirred to dissolve for 2 minutes; the concentration of xanthan gum is 50 mg / L, and the concentration of sodium caseinate is 200 mg / L; after the system is fully mixed, the metal copper is deposited on the cathode surface by electrodeposition, the cell voltage is 3.8 V, the electrolysis temperature is 10 ° C, and the time is 10 seconds, and the obtained product is a porous copper foil with good morphology.

[0054] Example 3

[0055] Stainless steel is used as cathode, and the cathode shape is sheet-shaped; gold is used as anode, and the anode shape is sheet-shaped; a mixed aqueous solution of sulfuric acid and copper sulfate is used as electrolyte, wherein the concentration of sulfuric acid is 90g / L, and the concentration of copper sulfate is 70g / L (in terms of copper ions); xanthan gum, sodium caseinate and glycerol are mixed in proportion, and glycerol accounts for 50% of the total volume; water accounting for 80% of the total volume is added, and a mixed aqueous solution of xanthan gum, sodium caseinate and glycerol is formed after stirring. The solution is added to the mixed aqueous solution of sulfuric acid and copper sulfate, and stirred to dissolve for 10 minutes; the concentration of xanthan gum is 0.5mg / L, and the concentration of sodium caseinate is 0.5mg / L; after the system is fully mixed, metal copper is deposited on the cathode surface by electrodeposition, the cell voltage is 2.4V, the electrolysis temperature is 25℃, and the time is 2min, and the obtained product is a porous copper foil with good morphology.

[0056] Comparative Example 1

[0057] This reference example is substantially the same as Example 1, except that sodium caseinate was not added.

[0058] If sodium caseinate is not added, the hydrosol system will be unstable and it will be difficult to form a stable network structure under high acidity conditions. In the absence of a stable template effect, the morphology of the porous copper foil obtained will be irregular.

[0059] Comparative Example 2

[0060] This control example is basically the same as Example 1, except that no xanthan gum is added.

[0061] Xanthan gum is the main substance that forms the hydrosol mesh structure in the electrolyte. Without xanthan gum, there will be no adsorption of the hydrosol mesh template on the electrode surface. The resulting porous copper foil has irregular morphology and poor structural continuity.

[0062] Comparative Example 3

[0063] This comparative example is substantially the same as Example 1, except that no glycerol was added.

[0064] Without the addition of glycerol, the dissolution of xanthan gum and sodium caseinate will become very difficult and the dissolution rate will be very slow, which is not conducive to the rapid development of experiments. At the same time, glycerol is also a hydrosol network structure enhancer, which can make the network template structure more stable. Without the addition of glycerol, the porous morphology of the copper foil will become irregular.

[0065] Comparative Example 4

[0066] This reference example is substantially the same as Example 1, except that the concentration of copper sulfate is 4 mg / L.

[0067] The concentration of copper sulfate affects the limiting current density during electrolysis. When the copper ion concentration is low, the electrolysis efficiency is low. In addition, under low copper ion concentration conditions, the nucleation rate of crystals is often greater than the growth rate, so the copper crystals on the surface of the porous copper foil are more delicate at lower copper ion concentrations.

[0068] Comparative Example 5

[0069] This reference example is substantially the same as Example 1, except that the concentration of copper sulfate is 150 mg / L.

[0070] Under conditions of higher copper sulfate concentration, the crystal growth rate is greater than the nucleation rate. If the current density is lower, the copper crystals on the surface of the porous copper foil will be coarser.

[0071] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0072] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made and that elements of the described embodiments may be substituted with substantial equivalents without departing from the spirit and scope of the present invention. In addition, many modifications may be made to adapt a particular situation or material to the teachings of the present invention without departing from the scope of the present invention. Therefore, it is not intended herein to limit the present invention to the specific disclosed embodiments for carrying out the present invention, but rather it is intended that the present invention will include all embodiments within the scope of the appended claims.

Claims

1. A method for preparing porous copper foil based on sodium caseinate enhanced electrodeposition, characterized in that: include: Mixing sulfuric acid and copper sulfate to form a mixed aqueous solution; Mix xanthan gum, sodium caseinate and glycerin, add water, and stir thoroughly to dissolve to form an aqueous solution containing xanthan gum, sodium caseinate and glycerin; The aqueous solution containing xanthan gum, sodium caseinate and glycerol is added to the mixed aqueous solution, and stirred and dissolved for 2 min to 30 min to obtain an aqueous solution system containing xanthan gum, glycerol, sodium caseinate, sulfuric acid and copper sulfate as an electrolyte, wherein the xanthan gum in the aqueous solution system is a network long-chain structure with sodium caseinate as a bridge; the concentration of sulfuric acid in the mixed aqueous solution is 20 g / L to 150 g / L, and the concentration of copper sulfate is 10 g / L to 120 g / L in terms of copper ions; the mass ratio of the glycerol in the total mass of the xanthan gum, sodium caseinate and glycerol is 30% to 90%; the concentration of the xanthan gum in the aqueous solution system is 0.5 mg / L to 200 mg / L, and the concentration of the sodium caseinate is 0.1 mg / L to 200 mg / L; The electrolyte, cathode and anode jointly construct an electrochemical reaction system; The porous copper foil is prepared by depositing metal copper on the cathode surface by electrodeposition. The process conditions of the electrodeposition method include: voltage of 1.0 V to 3.8 V, electrolysis temperature of 10° C. to 60° C., and time of 10 s to 5 min.

2. The method for preparing porous copper foil based on sodium caseinate enhanced electrodeposition according to claim 1, characterized in that: The volume ratio of water in the aqueous solution containing xanthan gum, sodium caseinate and glycerol is 40% to 95%.

3. The method for preparing porous copper foil based on sodium caseinate enhanced electrodeposition according to claim 1, characterized in that: The cathode is made of any one of copper, titanium and stainless steel.

4. The method for preparing porous copper foil based on sodium caseinate enhanced electrodeposition according to claim 1, characterized in that: The cathode may be in a sheet or cylinder shape.

5. The method for preparing porous copper foil based on sodium caseinate enhanced electrodeposition according to claim 1, characterized in that: The material of the anode includes an inert metal with an anti-corrosion coating on the surface, and the inert metal includes any one of titanium, gold and platinum.

6. The method for preparing porous copper foil based on sodium caseinate enhanced electrodeposition according to claim 1, characterized in that: The shape of the anode includes a sheet shape or an arc shape.

7. A porous copper foil having a porous surface obtained by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Electrolyte for preparing micron-sized porous copper foil through electrodeposition and method for preparing micron-sized porous copper foil through same

    CN108950607A

  • Graphite compounded copper foil and preparation method thereof

    CN110965085A